2020
DOI: 10.1111/hel.12698
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori eradication therapy outcome according to clarithromycin susceptibility testing in Japan

Abstract: BackgroundHelicobacter pylori (Hp) infection increases the risk of gastric cancer. Therefore, eradication is a global goal, which requires continuous monitoring of therapeutic regimens and effectiveness. Clarithromycin resistance is an important contributor to eradication failure, and metronidazole is recommended as second‐line treatment in such cases. Here, we retrospectively evaluated the clarithromycin and metronidazole resistance rates and treatment effectiveness in patients with Hp using tailored therapie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…Female sex was one of the indications for H pylori infection prevalence in our population. A recent study from Japan showed that clarithromycin resistance was higher in females 16 . Two ethnicities, African American and Hispanic, were predominant in our patient population.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…Female sex was one of the indications for H pylori infection prevalence in our population. A recent study from Japan showed that clarithromycin resistance was higher in females 16 . Two ethnicities, African American and Hispanic, were predominant in our patient population.…”
Section: Discussionmentioning
confidence: 45%
“…These were based on respective percentages seen for each of these factors within our H pylori patients as well as those reported in the literature. For example, it has been reported that females and African American and Hispanic races have a higher probability of getting H pylori infection 16,17 . The lower panel indicates major factors that influence the eradication of H pylori ; filled circles indicate factors reducing eradication.…”
Section: Resultsmentioning
confidence: 99%
“…In clinic, the importance of either H. pylori eradication or their regulation impose significant impact on either gastric cancer prevention or gastric diseases amelioration, for which several kinds of intervention like natural products, probiotics, and more effective anti-H. pylori therapy are under active investigation. (68)(69)(70)(71) In conclusion, walnut seems to be very effective and attractive because of well-acknowledgement as "pharmanutrient" against H. pylori infection. However, welldesigned clinical trial should be followed.…”
Section: Discussionmentioning
confidence: 96%
“…However, because susceptibility to clarithromycin was not considered, we further analyzed the results by taking susceptibility into account, given that many Japanese are resistant to clarithromycin. 21 As shown in Table 3, we used multinomial logistic regression because the dependent variable was divided into three levels: one, two, and three or more eradication attempts. Model 1 is the crude model.…”
Section: Discussionmentioning
confidence: 99%